2007
DOI: 10.1007/s00216-007-1435-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pesticide residue in grape juices and the effect of natural antioxidants on their degradation rate

Abstract: Various studies have been drawn toward the beneficial properties of fruit juices because they have several components, such as phenols, vitamins, and flavonoids, with antioxidant effects. However, fruit juices can also contain residues of pesticides used as standard pest control methods in crops. Many of these pesticides are degraded through oxidative mechanisms, and their persistence in juices can be enhanced by antioxidants. This study covers the degradation of four pesticides, aldicarb, demeton-S-methyl, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Food composition and processing have a significant effect on the dissipation of pesticide residues. Pico and Kozmutza (2007) studied the effect of natural antioxidants Ticha et al (2008) and Fenoll et al (2009b) investigated the dissipation of various insecticides and fungicides in apples and in peppers, respectively. They have reported that pesticide residue contents were decreased during storage.…”
Section: Resultsmentioning
confidence: 99%
“…Food composition and processing have a significant effect on the dissipation of pesticide residues. Pico and Kozmutza (2007) studied the effect of natural antioxidants Ticha et al (2008) and Fenoll et al (2009b) investigated the dissipation of various insecticides and fungicides in apples and in peppers, respectively. They have reported that pesticide residue contents were decreased during storage.…”
Section: Resultsmentioning
confidence: 99%
“…herbal infusions to treat various ailments and serious diseases [5]. P. juliflora is an ornamental traditional medicinal tree.…”
Section: Medicinal Plants Have Been Used Orally and As --------------mentioning
confidence: 99%
“…The most critical variable in SPE is the selection of the sorbent material. Among the packing materials available, reversed-phase octadecyl silica (RP-C18) (Chusaksri, Sutthivaiyakit, & Sutthivaiyakit, 2006;Hengel & Miller, 2007;Perreau et al, 2007;Picó & Kozmutza, 2007;Pitarch et al, 2007;Rodrigues et al, 2007;Esparza, Moyano, & Galceran, 2009) decyl silica (RP-C8) (Rodrigues et al, 2007), Oasis HLB (Gilbert-López et al, 2007a,b;Potter, Mohamed, & Ali, 2007;García-Reyes et al, 2008;Gervais et al, 2008;Ibáñez et al, 2008;Marín et al, 2009), Oasis MCX , cation exchange/reverse phase mixed-mode Nexus ABS (Hengel & Miller, 2007;Hengel & Miller, 2008), graphitized carbon (Pang et al, 2006b), aminopropyl (-NH 2 ) adsorbents with weak anionexchange and polar capabilities (Pang et al, 2006b;Hengel & Miller, 2008), Florisil (Tahboub, Zaater, & Barri, 2006;Zhang et al, 2006;Rissato et al, 2007;Garrido Frenich, Plaza-Bolaños, & Martínez Vidal, 2008) polystyrene-divinylbenzene materials (Marín et al, 2006;Perreau et al, 2007;Rodrigues et al, 2007;Kuster et al, 2008;Nanita, Pentz, & Bramble, 2009) and carbon-nanotubes (Wang et al, 2007b) have been reported (Tables 1 and 2). Recently, comprehensive studies comparing different SPE packing materials have been carried out in water and food matrices (Rodrigues et al, 2007;González-Rodríguez et al, 2008;…”
Section: A Sample Preparationmentioning
confidence: 99%